Obrnjeno učenje in poučevanje kot priložnost za inovativno in prožno izvajanje učnih oblik v visokošolskem izobraževanju - Plešec Gasparič, Romina; Valenčič Zuljan, Milena; Kalin, Jana (Revija za elementarno izobraževanje, 2020)
Flipped learning and teaching as an opportunity for innovative and flexible implementation of student groupings in higher education. Quality assurance in higher education includes the question of the ratio between direct and indirect higher education teaching. The didactic innovation flipped learning and teaching, which is being intensely researched in international university settings, enables the higher education teacher to carry out student grouping in a more flexible and innovative manner. This can contribute to student’s self-regulation of study, cognitive activity, improvement of academic achievements, and more appropriate time burden. It can also facilitate student’s higher conceptions of knowledge and collaborative skills. In this article, the authors define the advantages and disadvantages of various student groupings and explain flipped learning and teaching.